Розробка компонентів інформаційної системи для вибору квіткового магазину та здійснення бронювання квітів - Бондаренко, К. О. (ХНУРЕ, 2024)
The flower delivery service has undergone extensive reengineering, transitioning from a traditional brick-and-mortar shop to a sophisticated information system built on the ASP.NET Core platform. This transformation aims to streamline customer orders, enhance delivery logistics, and ensure efficient communication. With successful verification, the system is now primed for deployment, promising optimized operations, enhanced customer satisfaction, and improved business outcomes.
Keywords: вибір квіткового магазину; бронювання квітів; інформаційна система; управління замовленнями; онлайн платформа